Comparison and validation of finite element analysis with a servo-hydraulic testing unit for a biodegradable fixation system in a rabbit model - ATALI, ONUR; HARTOMACIOĞLU, SELİM (CHURCHILL LIVINGSTONE, 2014)
The aim of this study was the biomechanical validation of three-dimensional finite element analysis (FEA) with a servo-hydraulic testing unit (STU) for a resorbable fixation system (RFS) in a rabbit model. Bilateral mandibular vertical body osteotomies (BMVBO) were performed in 15 female New Zealand rabbits. The animals were divided into three groups. The STU and FEA tests were done immediately after surgery in group 1 (1 day), at the first postoperative month in group 2, and at the third postoperative month in group 3. Both stress tests were carried out by applying vertical forces at the lower incisal edge, loading from 0 N force and increasing this until breakage occurred at the bone. The maximum forces that the hemimandibles could stand and the amount of deformation were recorded and analysed with the FBA and STU tests. We found the STU and FEA test results to be similar and that they could be used interchangeably for groups 1 and 3. However, the FEA results differed most from the real STU values in group 2 because of callus formation that had not ossified at the osteotomy line.
Keywords: biodegradable implant; biomechanics; finite element analysis; mandible; osteotomy; SPLIT RAMUS OSTEOTOMY; MANDIBULAR ANGLE FRACTURES; BIOMECHANICAL EVALUATION; ORTHOGNATHIC SURGERY; SCREW FIXATION; TITANIUM PLATE; STABILITY; MANDIBLES; IMPLANTS; SHEEP